ANALISIS KONTRIBUSI PAJAK REKLAME DAN PAJAK HIBURAN - Pipit Mutiara; Intan Noor Fauziah; Catur Martian Fajar (Jurnal Financia : Akuntansi dan Keuangan, 2022)
The regional autonomy system in Indonesia makes local governments need to make efforts to increase their regional revenue sources. Regional Original Revenue is revenue that is used as a source of costs in all forms of government activities. Local taxes that can contribute to increasing local revenue are advertisement taxes and entertainment taxes, as evidenced by the growing development of the tourism sector which can encourage the growth of entertainment venues and the development of the goods and service company sector that uses advertising media in Cimahi City along with the growth of development. The city of Cimahi is growing rapidly. The purpose of this study was to determine the effect of the advertisement tax and entertainment tax on Regional Original Income in Cimahi City. The research method used is descriptive and verification methods with a quantitative approach. The results showed that the advertisement tax had a partially insignificant effect on Regional Original Income. Entertainment tax partially significant effect on local revenue. Simultaneously, the advertisement tax and entertainment tax have a significant effect on Local Original Income in Cimahi City.